2012
DOI: 10.1111/j.1600-0528.2011.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Demand for and utilization of dental services according to household income in the adult population in Norway

Abstract: Differences in demand for dental services according to household income are small, and there are no differences in utilization according to income. The findings are interesting, because in a population in which people have to pay almost all the costs for dental treatment themselves, one would expect the income differences in demand and utilization to be greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 34 publications
7
34
3
4
Order By: Relevance
“…Rather similarly, in Sweden, € Osterberg et al (23) found that the use of oral health care services had increased rather equally in income groups and the effect of income on the use had not changed 10 years after the implementation of subsidization reform. In addition, results from Norway showed that the income level was not associated with the use despite the minimal subsidization of dental care (45). On the other hand, our results suggest that the association between the income and regular dental visiting habit weakened slightly after the reform (Table 4).…”
Section: Discussioncontrasting
confidence: 75%
“…Rather similarly, in Sweden, € Osterberg et al (23) found that the use of oral health care services had increased rather equally in income groups and the effect of income on the use had not changed 10 years after the implementation of subsidization reform. In addition, results from Norway showed that the income level was not associated with the use despite the minimal subsidization of dental care (45). On the other hand, our results suggest that the association between the income and regular dental visiting habit weakened slightly after the reform (Table 4).…”
Section: Discussioncontrasting
confidence: 75%
“…Socioeconomic inequality in the access to dental care services has been confirmed in a number of countries [6,7,8,9,10,11,19,20,21], while the influence of country-specific health insurance systems has also been suggested [8,22,23]. Therefore, we think it would be meaningful and interesting to clarify the impact of SES (socioeconomic status) on the access to dental care services in Japan, where a universal insurance system has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism behind the link between poor oral health and low SES has not been fully elucidated, lack of access to dental care services in low SES groups is considered one of the causes of oral health inequality [5]. In fact, associations between lower SES and decreased access to dental services have been found in several countries [6,7,8,9,10,11]. However, a comparative study investigating access to dental services among European countries detected a different impact of SES, probably due to the impact of country-specific health insurance systems [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous findings in the Nordic countries, the majority of adults visit a dentist on a regular 12‐month basis, whereas younger people attend less often. This may reflect generational differences in preferences and needs related to health and oral health …”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Survey of Health, Ageing and Retirement in Europe (SHARE), Listl reported on considerable income‐related inequalities in dental service utilization among elderly across several countries. In Norway, similar income‐related inequalities are low or not existing . Social predictors of dental care utilization have been identified among Norwegian and Swedish community‐dwelling older adults .…”
mentioning
confidence: 99%